Effects of Interactive Vaulting for Children with Social and Behavioral Needs - Lee, Grace TV (East Carolina University, 2019)
This study explored the association of interactive vaulting with the social and behavioral skills of children with special needs. A one group quasi-experimental study was utilized to determine whether there were improvements or deterioration in the social and behavioral skills of the children participating in interactive vaulting. Following a completed BRIEF-2 pre- and post-test by the parents of the seven children in the interactive vaulting program, paired mean t-tests indicated that the social and behavioral skills of the children declined during the interactive vaulting intervention. However, none of the changes in the pre-test and post-test were statistically significant at the p < 0.05 level. As one of the first research studies in interactive vaulting, continued research of interactive vaulting and additional interventions for children with special needs are encouraged. Discussions regarding the implications of interactive vaulting and suggestions for future research are provided.
Keywords: interactive vaulting; social skills; behavioral skills; children with special needs